Penerapan Model Pembelajaran STAD untuk Meningkatkan Hasil Belajar Matematika Peserta Didik Kelas XI-4 di SMAN 6 Surabaya pada Pokok Bahasan Vektor - Dhea Ayu Sekar Utami; Anik Kirana; Sri Suratni (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
This research aims to describe the application of the Student Team Achievement Division (STAD) learning model in improving the learning outcomes of class XI-4 students at SMA Negeri 6 Surabaya, especially on the subject of vectors. The background to this research is strengthened by the fact that motivation to learn mathematics tends to be low, especially when studying complex material such as vectors. This is supported by initial observations which show that students often have difficulty understanding these concepts, which is reflected in the low learning outcomes, with a percentage of only 73%, and classical completeness of only 40%. This research is classroom action research carried out in two cycles. The research subjects consisted of 36 students. Data is collected through tests and observations. Data analysis was carried out using qualitative and quantitative descriptive techniques. The results in cycle 1 showed a significant improvement, with learning outcomes reaching 97% and classical completion increasing to 94%. In cycle 2, learning outcomes reached 98% and classical completion reached 100%. Thus, it can be concluded that the application of the STAD learning model is effective in improving the learning outcomes of class XI-4 students at SMA Negeri 6 Surabaya.